2020
DOI: 10.21203/rs.3.rs-25021/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aneuploid circulating tumor endothelial cells (CTECs) affect the detection of CTC, but they are fundamentally different

Abstract: Background Aneuploidy is an important criterion for tumor cell identification. Like CTCs (circulating tumor cells), many CTECs (circulating tumor endothelial cells) have chromosomal aneuploidy. Affected by tumor microenvironment and detection method, the only identification index CD31 may not be comprehensive enough, which greatly affects the accuracy of CTCs detection. Methods Here, we explored the number distribution, expression of surface tumor markers and chromosome ploidy differences of aneuploid CTECs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…Statistical analysis showed that there was no significant difference in CTCs and CTECs levels between the lung benign disease group and the healthy group. CTCs and CTECs levels of NSCLC patients was significantly higher than that of benign lung diseases and healthy group, which is consistent with previous studies [13,14,43]. Among the patients with different pathological types of NSCLC in this study, there was no statistically significant difference between pathological types, which is consistent with previous studies [13,44].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Statistical analysis showed that there was no significant difference in CTCs and CTECs levels between the lung benign disease group and the healthy group. CTCs and CTECs levels of NSCLC patients was significantly higher than that of benign lung diseases and healthy group, which is consistent with previous studies [13,14,43]. Among the patients with different pathological types of NSCLC in this study, there was no statistically significant difference between pathological types, which is consistent with previous studies [13,44].…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, between healthy and lung benign disease group, significant differences were found not only in the number of cells but also in the proportion of karyotypes in CTCs or CTECs. As for the source of non-hematologic aneuploid cells in the peripheral blood in normal people, some research suggested that occasional CD31+ aneuploid circulating endothelial cells in the blood of normal people are mainly from stromal cell trans-differentiation or cell aging, which is unrelated to tumor and can be cleared by the body's immune system [43]. But why did these non-hematologic aneuploid cells in the peripheral blood increased, when suffered benign lung disease such as pulmonary nodules, remains further research.…”
Section: Discussionmentioning
confidence: 99%